Morphological characters and phylogenetic analysis reveal a new species of Phellinus with hooked hymenial setae from Vietnam - Zhu, Lin; Ji, Xing; Si, Jing; Cui, Bao-Kai (Phytotaxa, 2018)
Phellinus vietnamensis sp. nov. is described from Vietnam based on morphological characters and molecular data. Morphologically, it is characterized by perennial, pileate basidiomata, a dimitic hyphal system, hooked hymenial setae, and colorless, broadly subglobose to ovoid, thick-walled basidiospores 5.5–6 × 4.8–5.2 μm. Phylogenetically, the status of Phellinus vietnamensis is strongly supported based on sequences of the nuclear internal transcribed spacer (ITS) regions, the translation elongation factor 1-α gene (EF1-α) nuclear large subunit rDNA (nrLSU) and the second largest subunits of RNA polymerase II (RPB2).